Application of Science, Technology, Engineering, Art, and Mathematics to Improve Critical Thinking Skills of Children Aged 4-5 Years - Raodah Kusumawaty Ramli; Riskal Fitri; Andi Rezky Nurhidaya; Sidrah Afriani Rachman (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
The low ability of children's critical thinking is caused by various things, one of which is the limitations of educators in providing space for students to stimulate necessary thinking skills in the learning process. The learning approach, methods, and media have yet to help children fully build critical thinking skills. Overcoming these problems is one way that can support the achievement of children's necessary thinking skills with the STEAM (Science, Technology, Engineering, Art, and Mathematics) learning model. This research method uses classroom action research methods to improve and increase the quality of learning regarding critical thinking skills. Based on the study results, there was an increase in all indicators of critical thinking in the development of student learning outcomes after being given action. The ability to think critically in children is evidenced by the average achievement category of Very Developed Children (BSB), with a percentage of in cycle one of 48.75% and in cycle two reaching 80.25%. The application of STEAM learning can improve critical thinking skills.